2020
DOI: 10.1177/0194599820942497
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Practice Characteristics of Otolaryngology Same‐Day Appointments in an Academic Center

Abstract: Objectives to Examine the practice characteristics of same-day clinic appointments and the use of same-day appointment scheduling to provide access to care in an otolaryngology–head and neck surgery clinic. Methods Retrospective chart review of same-day clinic appointments from January 1, 2016, to December 31, 2018, in patients aged >19 years at a single academic center. Demographic data, diagnoses, procedures completed, and operations completed were analyzed. Results There were 2696 visits by 2324 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
(21 reference statements)
2
2
0
Order By: Relevance
“…First, men were more likely to have walk-in visits than women. This result was similar to the findings of Riedl et al (2018) and Geelan-Hansen et al (2021), who observed a higher incidence of walk-in by men than by women [ 5 , 16 ]. This result is consistent with the view that men visit the dental emergency department more often than women owing to their higher risk of trauma while practicing outdoor activities such as sports or driving.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, men were more likely to have walk-in visits than women. This result was similar to the findings of Riedl et al (2018) and Geelan-Hansen et al (2021), who observed a higher incidence of walk-in by men than by women [ 5 , 16 ]. This result is consistent with the view that men visit the dental emergency department more often than women owing to their higher risk of trauma while practicing outdoor activities such as sports or driving.…”
Section: Discussionsupporting
confidence: 92%
“…Second, patients in the 20–29 and 30–39 age groups were more likely to visit the hospital without an appointment, and this result was similar to the high rate of 19–35-year-old walk-in patients observed by Geelan-Hansen et al (2021) [ 16 ]. Moreover, this result is also similar the finding of Riedl et al (2018), who reported a higher probability of walk-in patients at younger ages [ 5 ].…”
Section: Discussionsupporting
confidence: 80%
“…6,7 Reserving a few appointment slots, one in the morning and one in the afternoon that the electronic medical record releases the day prior, that are dedicated to same-day scheduling within 24 hours of the patient calling allows for improved rapid access while reducing the potential for overbooking providers. 5 This is the first study which assesses characteristics of otolaryngology same-day appointments for pediatric patients.…”
Section: Discussionmentioning
confidence: 99%
“…Characteristics of adult same-day visits have been assessed for common diagnoses along with resulting procedures and surgeries; however, this has not been completed for a pediatric population. 5 The goal of this study is to assess characteristics of same-day pediatric visits in an otolaryngology department at an academic institution.…”
Section: Introductionmentioning
confidence: 99%